2013
DOI: 10.1002/ijc.27985
|View full text |Cite
|
Sign up to set email alerts
|

Increasing participation in cervical cancer screening: Telephone contact with long‐term non‐attendees in Sweden. Results from RACOMIP, a randomized controlled trial

Abstract: Non-participation is the foremost screening-related risk factor for cervical cancer. We studied the effectiveness and costeffectiveness of an intervention to increase participation in the context of a well-run screening program. Telephone contact with non-attendees, offering an appointment to take a smear, was compared with a control group in a population-based randomized trial in western Sweden. Of 8,800 randomly selected women aged 30-62, without a registered Pap smear in the two latest screening rounds, 4,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 33 publications
9
49
2
1
Order By: Relevance
“…A study conducted in Malaysia also showed the lack of a proper follow‐up system for women taking screening tests . Annual reminders and scheduled appointments (with internet‐based rebooking of appointments) have already been implemented in Sweden . Organized programs that are implemented within existing health services, and include tools such as systematic call, recall, follow‐up, and surveillance, could also help to improve cervical cancer screening …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Malaysia also showed the lack of a proper follow‐up system for women taking screening tests . Annual reminders and scheduled appointments (with internet‐based rebooking of appointments) have already been implemented in Sweden . Organized programs that are implemented within existing health services, and include tools such as systematic call, recall, follow‐up, and surveillance, could also help to improve cervical cancer screening …”
Section: Discussionmentioning
confidence: 99%
“…13,14 Annual reminders and scheduled appointments (with internet-based rebooking of appointments) have already been implemented in Sweden. 15 Organized programs that are implemented within existing health services, and include tools such as systematic call, recall, follow-up, and surveillance, could also help to improve cervical cancer screening. 16 Nonetheless A study in Iran found that only 2% of women had been encouraged by radio and television broadcasts to take a cervical smear test.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond modeling analyses, few clinical studies have assessed the effectiveness of interventions using health outcomes, but were unable to report on long‐term endpoints such as life expectancy, given the considerable time lag between detection and cancer‐related death. A recent Swedish randomized controlled trial registered upfront costs of a telephone‐based intervention and reported resource use in terms of total cost per additional detected case of high‐grade precancer . By applying a “rule of thumb” for the ratio of treated high‐grade lesions to averted CC case, the authors concluded that the telephone‐based intervention would likely be cost‐saving.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Swedish randomized controlled trial registered upfront costs of a telephone-based intervention and reported resource use in terms of total cost per additional detected case of high-grade precancer. 25 By applying a "rule of thumb" for the ratio of treated high-grade lesions to averted CC case, the authors concluded that the telephonebased intervention would likely be cost-saving. Although such empirical studies are needed, only a relatively short time horizon and a limited number of scenarios are feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Telephone call A study performed in Sweden comprising 8,800 women who had not undergone Pap smear exam for two years, using control and intervention groups, inferred that telephone calls increased women's participation in the uptake of the exam, are low cost, and can be carried out within the scope of a prevention program (11) . Automated call reminders were used in another cohort study in Texas, United States of America, comprising 32,807 women for a three-year period, which also showed an increased uptake of Pap smear exam (12) .…”
Section: Case Managermentioning
confidence: 99%